Daniel X : Demons and Druids - James Patterson; Adam Sadler (Daniel X series bk, 2010)
As Daniel X continues to hunt for intergalactic aliens, he and his friends go to England searching for Beta, an outlaw who takes the form of fire and who killed Daniel's parents when he was two years old.